2021
DOI: 10.3390/risks9050089
|View full text |Cite
|
Sign up to set email alerts
|

Information-Theoretic Measures and Modeling Stock Market Volatility: A Comparative Approach

Abstract: The volatility analysis of stock returns data is paramount in financial studies. We investigate the dynamics of volatility and randomness of the Pakistan Stock Exchange (PSX-100) and obtain insights into the behavior of investors during and before the coronavirus disease (COVID-19 pandemic). The paper aims to present the volatility estimations and quantification of the randomness of PSX-100. The methodology includes two approaches: (i) the implementation of EGARCH, GJR-GARCH, and TGARCH models to estimate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 66 publications
1
24
0
Order By: Relevance
“…The recent pandemic also had a negative effect on volatility in the market. Research papers around the world show an increase in volatility coinciding with the outbreak of the pandemic (Ali et al 2020;Barro et al 2022;Chowdhury et al 2021;David et al 2020;Mishra and Mishra 2021;Sheraz and Nasir 2021;Uddin et al 2021). Gao et al (2021) find that the impact of COVID-19 on the stock market showed a significant leverage effect in both the US and China, imposing a stronger effect on the stock market volatility when it was already high.…”
Section: Literature Reviewmentioning
confidence: 97%
“…The recent pandemic also had a negative effect on volatility in the market. Research papers around the world show an increase in volatility coinciding with the outbreak of the pandemic (Ali et al 2020;Barro et al 2022;Chowdhury et al 2021;David et al 2020;Mishra and Mishra 2021;Sheraz and Nasir 2021;Uddin et al 2021). Gao et al (2021) find that the impact of COVID-19 on the stock market showed a significant leverage effect in both the US and China, imposing a stronger effect on the stock market volatility when it was already high.…”
Section: Literature Reviewmentioning
confidence: 97%
“…In addition, the damaging effect of this pandemic was also found in stock market volatility. Research on stock markets around the world reveals an increase in volatility following the COVID-19 pandemic (Chowdhury et al , 2021; David et al , 2021; Mishra and Mishra, 2021; Sheraz and Nasir, 2021; Uddin et al , 2021). According to Fakhfekh et al (2021), this volatility persisted in Tunisia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers generally find that companies have a motive to disclose risk information as it benefits investors, enabling companies to better allocate resources. Measuring and managing financial risk represent key concerns of investors (Sheraz and Nasir 2021). Therefore, within the current environment, the motivation concerning risk disclosure is determined by the circumstances in which risk disclosure is important, specifically when the risk level of investment is high (Abraham and Cox 2007;Linsley and Shrives 2006), entailing pressure on companies to attract financial analysts (Sundgren et al 2018;Lehavy et al 2011), investors, and professionals (Abraham and Shrives 2014).…”
Section: Literature Reviewmentioning
confidence: 99%